2014
DOI: 10.1186/1471-2180-14-165
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of amikacin, kanamycin and capreomycin resistance in M/XDR-TB strains isolated in Thailand

Abstract: BackgroundThe emergence of multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) makes the treatment and control of tuberculosis difficult. Rapid detection of drug-resistant strains is important for the successful treatment of drug-resistant tuberculosis; however, not all resistance mechanisms to the injectable second-line drugs such as amikacin (AK), kanamycin (KM), and capreomycin (CAP) are well understood. This study aims to validate the mechanisms associated with AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 39 publications
5
34
0
Order By: Relevance
“…Upon completion of the present study, Rodwell et al determined through Sanger sequencing that the majority of the KAN isolates examined in their study that had no rrs 1401 SNPs had SNPs in the eis promoter (18). Undetected eis promoter mutations, along with recently reported mutations in whiB7 gene regions (42)(43)(44), might be responsible for the observed KAN-resistant phenotypes that were not detected by our PSQ assay. Adding the eis promoter region as a PSQ target in a future version of the PSQ assay should considerably improve its sensitivity for detecting KAN resistance in any location where these SNPs are prevalent.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Upon completion of the present study, Rodwell et al determined through Sanger sequencing that the majority of the KAN isolates examined in their study that had no rrs 1401 SNPs had SNPs in the eis promoter (18). Undetected eis promoter mutations, along with recently reported mutations in whiB7 gene regions (42)(43)(44), might be responsible for the observed KAN-resistant phenotypes that were not detected by our PSQ assay. Adding the eis promoter region as a PSQ target in a future version of the PSQ assay should considerably improve its sensitivity for detecting KAN resistance in any location where these SNPs are prevalent.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, as discussed in Sirgel et al (40), clinical isolates from South Africa with the 1401 A-G mutation in the rrs gene showed decreased phenotypic susceptibility to CAP. Furthermore, while the rrs 1401 A-G mutation is implicated in cross-resistance to all three injectable drugs, some studies have shown that mutations outside our considered genomic regions, most notably mutations in eis promoter and tlyA, may independently confer resistance to KAN and CAP, respectively (41)(42)(43)(44). The sensitivity and specificity of PSQ for detecting phenotypic CAP and KAN resistance are likely to remain at Ͻ100% unless the CAP critical concentration issue is addressed independently of the PSQ platform, and other gene regions are added to the PSQ assay.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the overexpression of the eis gene, which encodes an aminoglycoside acetyltransferase, is associated with low-level kanamycin resistance [38e40]. Mutations within the eis promoter region were reported in 26e80% of TB patients with kanamycin resistance [38]. In Korea, eis gene mutations were found in 13.7% of TB patients with kanamycin resistance, and those mutations demonstrated crossresistance with other injectable drugs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Oligonucleotide primers used for polymerase chain reaction (PCR) amplification and sequencing of rpsL , rrs , gidB , and whiB7 were based on previous studies or newly designed in the present study (Table 2)1718192021. Amplifications were carried out using Pfu DNA polymerase (Bioneer Corp., Daegeon, Korea).…”
Section: Methodsmentioning
confidence: 99%